2022
DOI: 10.1021/acsami.2c06783
|View full text |Cite
|
Sign up to set email alerts
|

Coating Bioactive Microcapsules with Tannic Acid Enhances the Phenotype of the Encapsulated Pluripotent Stem Cells

Abstract: Human pluripotent stem cells (hPSCs) may be differentiated into any adult cell type and therefore hold incredible promise for cell therapeutics and disease modeling. There is increasing interest in three-dimensional (3D) hPSC culture because of improved differentiation outcomes and potential for scale up. Our team has recently described bioactive heparin (Hep)-containing core–shell microcapsules that promote rapid aggregation of stem cells into spheroids and may also be loaded with growth factors for the local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Then total RNA was extracted and purified by using a RNeasy Plant Mini Kit (Qiagen, Valencia, CA, USA) following manufacturer's instructions. cDNA was synthesized with a QuantiTect Reverse Transcription Kit (Roche, Basel, Switzerland), and quantitative real-time RT-PCR was performed with the QuantStudio™ 5 System (Thermo Scientific Inc.) using universal SYBR Green Master (Roche) [ 34 , 44 ]. Relative gene expression was calculated using the comparative threshold cycle (ΔΔCT) method and normalized with glyceraldehyde 3-phophate dehydrogenase (GAPDH) as a housekeeping gene.…”
Section: Methodsmentioning
confidence: 99%
“…Then total RNA was extracted and purified by using a RNeasy Plant Mini Kit (Qiagen, Valencia, CA, USA) following manufacturer's instructions. cDNA was synthesized with a QuantiTect Reverse Transcription Kit (Roche, Basel, Switzerland), and quantitative real-time RT-PCR was performed with the QuantStudio™ 5 System (Thermo Scientific Inc.) using universal SYBR Green Master (Roche) [ 34 , 44 ]. Relative gene expression was calculated using the comparative threshold cycle (ΔΔCT) method and normalized with glyceraldehyde 3-phophate dehydrogenase (GAPDH) as a housekeeping gene.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, fewer TAs were chemically bonded on PNIPAAm 2000 -APTES-TA and PNIPAAm 1300 -APTES-TA, which caused easy TA release. Overall, the TA-modified hydrogel coatings on PNIPAAm 860 -APTES-TA and PNIPAAm 500 -APTES-TAare relatively stable in the long term, which may be better suitable for maintaining the protein on coatings [25,34]. tween TAs may be so large that it is difficult to form mutual overlaps of TAs and the stable cross-linking networks of TA may not be created.…”
Section: Stability Of Ta-modified Hydrogel Coatingsmentioning
confidence: 99%
“…For example, Revzin et al reported that ultrathin TA-coated heparin microgels were able to capture about two times the basic fibroblast growth factor (BFGF) compared to bare heparin microgels. The BFGF release was prolonged by 1–2 d, inducing human pluripotent stem cells to express a higher level of pluripotency [ 25 ]. Therefore, TA was incorporated into PNIPAAm coatings, potentially endowing the coating with the ability to mediate protein behaviors and elevate cell adhesion without the need for rigorous tailoring of coating thickness.…”
Section: Introductionmentioning
confidence: 99%